AN ANALYSIS OF THE RELATIONSHIP BETWEEN PERSONALITY AND ACADEMIC ACHIEVEMENTS IN TERTIARY INSTITUTIONS IN NORTH WESTERN NIGERIA - Umar, Muhammed (Academic Journal of Psychology and Education (AJPE), 2022)
This study aimed to investigate the relationship between personality variables and academic performance among higher institution students in northwestern Nigeria. The hypothesis tested in this study was that there is no significant difference between personality and course of study among higher institution students. A correlational design was employed, and a sample of 389 students from eight Colleges of Education in the region was drawn for data collection. The Eysenck Personality Inventory Scale was used to collect data on personality variables, while academic records were used to measure academic performance. An independent t-test was conducted at a significance level of 0.05 to determine the extent of differences between personality and students’ course of study. The findings revealed that there is no significant difference between Science and Arts students in their level of personality scores. The study recommends that personality of students should not be considered as a yardstick for allocating a course to students, but their interests and aptitudes should be given priority. It is essential to treat all students equally, irrespective of their personality types, to enhance their academic performance